Development of biodegradable plastic composite blends based on sago derived starch and natural rubber - Kiing, Sie Cheong; Balasubramaniam, Jaya Raj; Yiu, Pang Hung; Wong, Sie Chuong; Amarthalingam, Rajan (Universiti Putra Malaysia Press, 2010)
Polyethylene is a widely used packaging material, but its non-biodegradable nature can lead to waste disposal problems. This increases the concern in research and development of biodegradable plastics from natural resource as alternatives to petroleum-derived plastics. In this study, biodegradable plastic composites were prepared by blending thermoplastic starch with natural rubber in the present of glycerol as plasticizer. Local sago starch was cast with 0.5 to 10% of natural rubber to prepare the bioplastic. The products were characterized by differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR), water absorption test, biodegradable test, hydrolysis test, and mechanical analysis. Meanwhile, composite with natural rubber latex was increased from 0.5 to 10% showing that the melting temperature is in the range of 120 to 150 °C, but with no significant difference. The water absorption characteristics, biodegradability, and tensile strength decreased by 11.21%, 30.18%, and 20.733 MPa, respectively. However, the elongation at break was increased from 26.67 to 503.3%. The findings of this study showed that sago starch has a great potential in bioplastic production with good miscibility and compatibility.